DESolution of CD and CB Macrocycles. Issue 36 (9th June 2017) - McCune, Jade A.; Kunz, Susanna; Olesińska, Magdalena; Scherman, Oren A.
Abstract: Supramolecular chemistry utilizing the macrocyclic hosts cyclodextrins (CDs) and cucurbit[ n ]urils (CB[ n ]s) is traditionally performed in aqueous media; however, their solubility is typically poor, especially for the family of CB[ n ]s. Through derivatization of these macrocycles their solubility can be augmented to enable enhanced solubility in water and in some organic solvents. The increase in solubility of these derivatized macrocycles allows for their use in a wider range of chemical environments and giving rise to myriad potential applications. The dissolution of parent CDs (α‐, β‐ and γ‐) and CB[ n ]s ( n =6–8) in deep eutectic solvents (DES) is reported, showing dramatic enhanced solubility of the larger species in both families, CB[7] and CB[8] as well as β‐ and γ‐CD, respectively. Furthermore, the host–guest properties are maintained in this new solvation medium. Abstract : Supramolecular DESolution : Significantly high solubilities of cyclodextrins (CDs; α‐, β‐ and γ‐) and cucurbit[ n ]urils (CB[ n ]s; n =6–8) are exhibited in a choline chloride (ChCl)–urea deep eutectic solvent (DES). β‐ and γ‐CDs were soluble at >1 g mL −1 DES, resulting in 50 wt % solutions. Additionally, the solubility of CB[ n ] is also found to be significantly enhanced, extending the range of CB solubility into alkaline media for the first time. The host–guest chemistry of these macrocycles is maintained upon dissolution in these highly ordered solvents.